If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.5x = 65 + 9x Solving 2.5x = 65 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 2.5x + -9x = 65 + 9x + -9x Combine like terms: 2.5x + -9x = -6.5x -6.5x = 65 + 9x + -9x Combine like terms: 9x + -9x = 0 -6.5x = 65 + 0 -6.5x = 65 Divide each side by '-6.5'. x = -10 Simplifying x = -10
| 2x-5y+5=0 | | -5x^4-2s^3+18=0 | | 6•(-5/3) | | (-2x+10)-(6x+5y+12)+(x+8y-16)= | | 13h+13(3h)= | | 25-13+x-7+120=135 | | 56+2w=9w | | -2(4x+3)+2x=12 | | t+17=33 | | -7=-5x+3 | | (5^2/3)^3y | | 2.9x+59.9=35.5-9.3x | | 4(2-m)+8m=3 | | X-4+5X=32 | | 2x^6+8x^5+5x^4+7x^3+13x^2+0x+23=0 | | 4+10n-3=4n+49-2n | | c/9=11 | | cos(a)=-1 | | 3/14=x-2/42 | | 8=2+2j | | y-4.5=1 | | v-2.5=5.5 | | 5(x-3)+4x= | | 8-2k=2 | | 3s-17=-21+7s | | 9.7x=-78.57 | | 4x=3-3x | | -14a^0b^7c^6/6a^-5b^7c | | 25x^3/(-5x) | | 44+r=1 | | 2x+5-7=12-19 | | (x)(4x)=100 |